A Paradigm Shift in Brand Communication: Accentuating the Perception of the Youth of Gujarat Regarding Product Placement in Hindi Movies - Jayswal, Mitesh M.; Salvi, Priti (Indian Journal of Marketing, 2007)
High degree of brand proliferation in most of the product categories has compelled the advertising professional to think for some innovative ways for presenting the brands. In last two decades, the growing popularity of television has established TV commercials as the first choice of advertisers. In TV commercials, the problems of zapping and cluttered environment have created the necessity for finding a more effective ways for audiovisual presentation of brands. Increasing popularity of movies and multiplexes provides an opportunity to the marketers for targeting the mass audience having high level of involvement by weaving the brand with movie. This concept of brand promotion is known as product placement.From last decade, this idea of placing the brands in movies has grown very rapidly in India. It is not only an ideal medium for advertisers for effective promotion of respective brands but also for the movie producers to earn additional revenue. Producers can get benefit in various forms like in cash or promotion of movie as a media partner. In this paper the authors have identified some basic techniques, which are used by advertisers for placing the brands in Hindi movies. The authors have also verified the effectiveness of some of the popular methods of product placement and presented a model for product placement process. This paper can be useful to academicians as well as advertising professionals for this obscure topic.